PENYULUHANPELATIHAN ORIENTASI KEWIRAUSAHAAN BAGI PENGRAJIN FIGURA BINGKAI KAYU JATI RIZKYMARTAPURA - Sulastini Sulastini; Dewi Ariefahnoor; Adhi Surya (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
Entrepreneurial activity is not the result of an inheritance or a derivative talent parents alone, entrepreneurship can be taught and nurtured. The ability to create and use new knowledge on an ongoing basis is strongly influenced by the degree of entrepreneurial person. Therefore, entrepreneurship is defined ability to create and build a vision of something that does not exist and meaningful to humans through creative action and innovative measures to create business opportunities. Entrepreneurial action is manifested as an entrepreneurial orientation is behavior that reflected the behavior of the owner or craftsman through keinovasian, dare to take risks and proactivity. Given the importance of entrepreneurial orientation training to succeed as a business then craftsmen figura teak frame Rifky in Martapura Banjar district needs to develop entrepreneurship orientation in its business activities. Motifs, colors and designs are less attractive and less innovative so that interest figura teak frame is very less. Unlike the typical Java figura in addition to easily be everywhere also available in various designs, patterns and colors. In addition to expression differences with Java figura. It is necessary for the training effort for the craftsmen in Martapura Banjar district cultivate the spirit more active and resilient in the face of all obstacles either comes from internal and external craftsmen craftsmen, so figura teak able to increase revenues for craftsmen figura teak. Internal aspects indicated the failure of the craftsman among others the quality of the resource, setting the selling price is relatively high, the motives are less developed, deterioration of working capital and the increase in debt as a result of low accumulation of capital and the inability to find sources of capital cost, network limited business, the ability to innovate are less able. This information indicates internal weaknesses that have the potential to make an effort figura teak can fail.